Critical Synthesis Package: UCLA Geriatric Knowledge Test for Primary Care Residents - Godwin Y. Dogbey (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the University of California Los Angeles Geriatric Knowledge Test for Primary Care Residents (UCLA GKTPCR), and (2) a copy of the UCLA GKTPCR instrument and scoring key developed by David B. Reuben, MD, Ming Lee, PhD, Michelle Eslami, MD, and Daniel Osterweil, MD. The UCLA GKTPCR was designed to provide a reliable and valid tool to measure the geriatric content knowledge of primary care residents. This instrument is composed of 23 multiple-choice responses to both questions and incomplete statements. Only one answer to the multiple choices is deemed best and correct. While few studies were found that provided further validity evidence, the few that used the measure reported that the content, known-groups, and concurrent validity evidence were appropriate. Reported validity was average but consistent with similar instruments. The UCLA GKTPCR is easy to modify and has been used quite extensively across the health sciences field (e.g., nursing) and medical education in various contexts, often together with tools measuring geriatric attitude. It has been used in international contexts as well. The UCLA GKTPCR promises to gauge the geriatric knowledge across the entire continuum of medical education and even for instances involving continuing education of practicing physicians.